Protonated carbon nitride, preparation method thereof and application of protonated carbon nitride in lithium battery
By spin-coating the composite layer formed by protonated carbon nitride and polymer on the surface of lithium metal, the problems of interfacial layer in the interface modification of lithium metal negative electrode are solved, and the high stability and long-life performance of lithium batteries are achieved.
Patent Information
- Application Number
- CN202510433060.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-08
- Publication Date
- 2025-07-11
- Estimated Expiration
- 2045-04-08
AI Technical Summary
The prior art has problems such as uneven interface layer, poor ion transmission path, and poor material stability in the interface modification of lithium metal negative electrodes, resulting in short cycle life of lithium metal batteries.
An organic/inorganic protective layer combined with protonated carbon nitride and polymer is used to form a uniform C3N4-polymer composite layer on the surface of lithium metal by spin coating to improve the interface performance between the solid electrolyte and the lithium metal negative electrode.
It improves interface stability and long cycle performance, achieves rapid transmission and uniform deposition of lithium ions, and improves the overall performance of lithium batteries. Especially under the conditions of wide electrochemical windows and high ion migration, lithium metal batteries can be stable cycling for more than 2,000 hours.
Smart Images

Figure SMS_1 
Figure HDA0005348780650000011 
Figure HDA0005348780650000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and relates to a protonated carbon nitride, a preparation method thereof, and an application thereof in a lithium battery. Background Art
[0002] Lithium metal anodes face many challenges in practical applications, mainly including problems such as lithium dendrite growth, volume expansion, and pulverization during cycling. These problems cause lithium metal batteries to suddenly fail after a certain number of cycles. To overcome problems such as lithium dendrite growth and volume expansion, researchers have proposed various methods for modifying the interface of lithium metal anodes. For example, modifying the electrolyte bulk, optimizing the ionic conductivity and mechanical strength of the solid electrolyte by doping elements (such as Ta, Al, etc.) or introducing fast ion conductors (such as Li3N, Li7P3S 11 etc.), but the interface contact problem cannot be fundamentally solved, and the high mechanical strength will exacerbate the interface stress and cause cracks.
[0003] The prior art CN117317385A discloses a method for modifying the negative electrode interface in a solid-state lithium battery by using a composite two-dimensional material. By coating a precursor solution on the surface of the solid electrolyte, an interfacial intermediate layer is formed through an in-situ chemical reaction, thereby improving the interface contact. However, the method of coating on the surface of the solid electrolyte cannot ensure the uniformity of the interface layer, which will affect the ion transport path. And there is a compatibility problem between the precursor and the polymer matrix, resulting in easy peeling of the interface layer and unable to provide effective protection.
[0004] In-situ generating an SEI layer (such as Li3N, LiF or a polymer-based composite layer) on the lithium metal surface through chemical / electrochemical methods to optimize lithium ion transport and lithium metal deposition. However, the preparation process is relatively complex, requiring precise control of conditions and high usage costs.
[0005] The prior art CN114899362B discloses a three-dimensional lithium metal negative electrode material with a solid electrolyte interface and a preparation method thereof. By in-situ coating g-C3N4 on a three-dimensional carbon material and then performing a high-temperature melting reaction to in-situ form a Li3N artificial solid electrolyte interface film, the problem of lithium dendrite growth is effectively solved. However, the uniformity and compactness of the coating material will significantly affect the stability of the material. And the high-temperature melting reaction needs to be carried out in a glove box, with significant energy consumption costs and high process complexity, which is not conducive to large-scale production. Summary of the Invention
[0006] The purpose of the present invention is to provide a protonated carbon nitride, a preparation method thereof, and an application thereof in a lithium battery, which can effectively improve the interfacial performance between the solid electrolyte and the lithium metal negative electrode and achieve long-life energy storage.
[0007] To achieve the above object, the present invention adopts the following technical solutions:
[0008] A preparation method of protonated carbon nitride, comprising the following steps:
[0009] Grind the carbon nitride, soak it in an acidic solution, wash it until neutral, and then ultrasonically treat, exfoliate, and dry the washed carbon nitride to obtain protonated carbon nitride.
[0010] In one preferred embodiment, the preparation method of the carbon nitride is: calcine melamine in segments under an inert atmosphere to obtain carbon nitride;
[0011] The process of the segmented calcination is: the first-stage calcination temperature is 450 - 550 °C, the heating rate is 5 - 10 °C / min, and the time is 1 - 3 h; the second-stage calcination temperature is 600 - 750 °C, the heating rate is 5 - 10 °C / min, and the time is 1 - 3 h.
[0012] The role of the first-stage calcination is to form the basic structure of carbon nitride and convert melamine into carbon nitride. If the temperature is too low, melamine may not be fully converted into carbon nitride, resulting in insufficient crystallinity of the product; if the temperature is too high, it may cause excessive decomposition or structural collapse of carbon nitride, destroying its layered structure. The role of the second-stage calcination is to oxidize the carbon nitride, remove impurities in the carbon nitride, increase the porosity, and improve the specific surface area of the material. If the temperature is too low, the oxidation treatment is insufficient and impurities cannot be effectively removed. If the temperature is too high, too many defects or amorphous regions may be formed.
[0013] In one preferred embodiment, the flow rate of the inert gas is 40 - 60 mL / min.
[0014] In one preferred embodiment, the inert gas is argon, nitrogen, or helium.
[0015] In one preferred embodiment, the acidic solution is hydrochloric acid.
[0016] In one preferred embodiment, the concentration of hydrochloric acid is 3 - 6 mol / L.
[0017] In one preferred embodiment, the soaking time in the acidic solution is 1 - 2 h.
[0018] In one preferred embodiment, the carbon nitride is ground to a particle size of 25 - 75 μm.
[0019] In one preferred embodiment, the washing is carried out with distilled water.
[0020] In one preferred embodiment, the process of ultrasonic treatment is: work for 3 - 5 s, intermittent for 3 - 5 s, and the ultrasonic time is 1 - 3 h.
[0021] In one preferred embodiment, the exfoliation process is as follows: mixing carbon nitride with salt and ball-milling, with the ball-milling speed being 400 - 700 r / min and the ball-milling time being 2 - 4 h.
[0022] During the exfoliation process, salt particles are used as the grinding medium and template to achieve efficient exfoliation.
[0023] In one preferred embodiment, the salt is one or several of sodium chloride, ammonium sulfate, and potassium chloride.
[0024] In one preferred embodiment, the drying process is as follows: drying at 140 - 160 °C for 6 - 9 h.
[0025] In one preferred embodiment, the porosity of protonated carbon nitride is 20% - 30%.
[0026] An overly large porosity may lead to a reduction in the mechanical strength of the material, instability of the material structure, and affect its stability in practical applications. An overly small porosity will limit the ion transport and affect the electrochemical performance of the material.
[0027] In one preferred embodiment, the diameter of the micropores of protonated carbon nitride is 0.5 - 1 nm.
[0028] The micropores on protonated carbon nitride provide a high specific surface area and good lithium-ion adsorption performance. When the pores are too small (less than 0.5 nm), the overly small pores may lead to a reduction in the diffusion rate of lithium ions inside the material, and fast lithium-ion transport cannot be achieved. When the pores are too large (exceeding 2 nm), the specific surface area of the carbon nitride material will decrease, resulting in a reduction in the contact area with lithium ions. This will reduce the lithium-ion adsorption efficiency and affect the lithium-ion transport speed.
[0029] Based on a unified inventive concept, the present invention also claims the protonated carbon nitride prepared by the described preparation method.
[0030] Based on a unified inventive concept, the present invention also claims the application of the protonated carbon nitride in improving the interfacial performance between a solid-state electrolyte and a lithium metal anode.
[0031] Based on a unified inventive concept, the present invention also claims a polymer slurry, and the polymer slurry contains protonated carbon nitride.
[0032] In one preferred embodiment, by weight, the polymer slurry contains 1 - 5 parts of the protonated carbon nitride, 8 - 12 parts of an olefin polymer, and 3 - 8 parts of a lithium salt.
[0033] In one preferred embodiment, the olefin polymer is one or more of polyvinylidene fluoride, poly(vinylidene fluoride - hexafluoropropylene) copolymer, poly(vinylidene fluoride - trifluoroethylene) copolymer, poly(vinylidene fluoride - tetrafluoroethylene) copolymer, and poly(vinylidene fluoride - trifluoroethylene - chlorotrifluoroethylene) copolymer.
[0034] In one preferred embodiment, the lithium salt is one or more of LiCl, LiF, LiBr, LiI, Li2SO4, LiNO3, LiPF6, LiTFSI, LiFSI, and LiDFOB.
[0035] In one preferred embodiment, the polymer slurry further comprises 70 - 90 parts of a polar solvent.
[0036] In one preferred embodiment, the polar solvent is one or both of tetrahydrofuran and acetone.
[0037] Based on a unified inventive concept, the present invention also claims protection for a lithium metal negative electrode coated with the polymer slurry.
[0038] Based on a unified inventive concept, the present invention also claims protection for a solid - state battery comprising the lithium metal negative electrode.
[0039] Based on a unified inventive concept, the present invention also claims protection for a method of improving the interfacial performance between a solid - state electrolyte and a lithium metal negative electrode, comprising the following steps:
[0040] (1) Mix the protonated carbon nitride, olefin polymer, polar solvent, and lithium salt uniformly to obtain a polymer slurry;
[0041] (2) Spin - coat the polymer slurry on the surface of the lithium metal and dry it to obtain a lithium metal negative electrode;
[0042] (3) Assemble a positive electrode sheet, a polymer - based solid - state electrolyte, and the lithium metal negative electrode to obtain a solid - state battery.
[0043] In one preferred embodiment, the mixing is stirring, the stirring time is 6 - 14 h, and the temperature is 45°C - 70°C.
[0044] In one preferred embodiment, the rotation speed of the spin - coating is 200 - 600 r / min, the spin - coating thickness is 10 - 30 μm, and the drying time is 6 - 10 h.
[0045] In one preferred embodiment, the dew point of the environment for spin - coating and drying is less than - 50°C.
[0046] In one preferred embodiment, the thickness of the lithium metal is 80 - 120 μm.
[0047] In one preferred embodiment, the positive electrode is a nickel cobalt manganese oxide type positive electrode.
[0048] The beneficial technical effects of the present invention compared with the prior art are as follows:
[0049] 1. The present invention aims to provide a method and application for improving the interface between a solid electrolyte and a lithium metal negative electrode. By using protonated C3N4 and a polymer matrix as a protective layer and spin-coating it on the lithium metal interface, preparation and assembly are realized in a dry room. By coating an organic / inorganic protective layer of nitrogen-rich compounds - polymers on the lithium metal surface, the solid electrolyte interface is stabilized, effectively improving the interface stability and long-cycle performance.
[0050] 2. The present invention prepares carbon nitride by thermal polymerization + protonation. Through protonation treatment, the surface is positively charged, enabling it to be better dispersed in the solution. At the same time, the layered structure of carbon nitride is destroyed, forming more micropores with a size of 0.5 - 1 nm, providing a high specific surface area and good lithium-ion adsorption performance.
[0051] 3. The present invention uses a method of modifying with an organic / inorganic interface coating. A protonated nitrogen-rich C3N4 polymer solution is spin-coated on the negative electrode side of the lithium foil to improve the lithium metal negative electrode interface. Carbon nitride combines with the polymer to form a uniform C3N4 - polymer composite layer. This composite layer not only has good mechanical stability and ion conductivity, thus avoiding the grain boundary problems existing in the traditional solid electrolyte interface (SEI). At the same time, this composite interface layer can homogenize the current density and lithium-ion flux distribution, thereby inducing uniform deposition of lithium metal. In addition, protonated carbon nitride has an ordered microporous structure and high lithium-ion selectivity, which can provide a fast lithium-ion transport channel, reduce the tortuosity of the transport path, promote the uniform nucleation of lithium metal, further induce the uniform deposition of lithium metal, and improve the overall performance of the battery.
[0052] 4. The lithium solid-state battery proposed by the present invention with a lithium metal negative electrode with an organic / inorganic composite layer has a wide electrochemical window, a high ion transference number. The lithium-lithium symmetric battery can be stably cycled for 2000 h, the full battery can be stably cycled 1200 times at a room temperature of 2C rate, and the capacity retention rate > 80%. The assembled pouch battery with a lithium metal negative electrode with an organic / inorganic composite layer can achieve 160 stable cycles, which has great industrial application value. Description of the Drawings
[0053] Figure 1 It is the working principle diagram of the protonated lithium nitride - polymer coating prepared in the embodiment of the present invention.
[0054] Figure 2 It is the SEM image of the protonated lithium nitride prepared in Example 1 of the present invention.
[0055] Figure 3 It is a graph of the room temperature electrochemical window test results of the assembled half-cells in Example 1 and Comparative Example 1 of the present invention.
[0056] Figure 4 This is a room temperature stability test chart of the lithium metal symmetric battery modified by the assembled coating in Example 1 of the present invention.
[0057] Figure 5 The room temperature electrochemical performance of the lithium metal button cell modified by the assembled coating in Example 1 of the present invention at 2C.
[0058] Figure 6 It is a schematic diagram of assembling lithium metal pouch batteries in Examples 1-6 and Comparative Examples 1-11 of the present invention.
[0059] Figure 7 The room temperature electrochemical performance of the lithium metal pouch cell modified by the assembled coating in Example 1 of the present invention at 0.2C. DETAILED DESCRIPTION
[0060] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0061] Example 1
[0062] according to Figure 1 Working principle diagram of the preparation of protonated lithium nitride-polymer coating The process of preparing protonated lithium nitride-polymer coating is as follows:
[0063] Modification of lithium foil: (1) Commercial melamine powder was placed in a tubular furnace and calcined in stages under the protection of an argon atmosphere. The argon gas pressure valve was controlled so that the gas flow rate was 50 mL / min. The first stage calcination temperature was 500°C, and the heating rate was 5°C / min. The second stage calcination temperature was 650°C, and the heating rate was 5°C / min to obtain bulk carbon nitride.
[0064] (2) Grind the blocky carbon nitride obtained in step (1) into powder, remove impurities in a hydrochloric acid solution, wash with distilled water three times, measure the pH to be neutral, use the probe provided with the spin coater to sonicate for 2 hours, the working mode is 3 seconds on, 3 seconds off, and finally freeze-dry to obtain protonated carbon nitride.
[0065] (3) Weigh 0.05 g of the protonated C3N4 obtained in step (2) and dissolve it in 10 mL of tetrahydrofuran solvent. Weigh 0.25 g of poly(vinylidene fluoride - hexafluoropropylene) (PVDF - HFP, weight - average molecular weight of 400000) and 0.1 g of lithium bis(fluorosulfonyl)imide (LiFSI) and dissolve them in the above homogeneous solution. Stir at a temperature of 60 °C for 10 h to obtain a uniform polymer slurry;
[0066] (4) Place a 100 - μm lithium foil in a spin coater. Add the polymer slurry obtained in step (3) to the spin coater. The rotation speed of the spin coater is 400 r / min, and the spin - coating thickness is 20 μm. Let the lithium foil with the coating stand in a dry room for 8 h to obtain the modified lithium foil. The whole process is carried out in a dry room, and the dew point is required to be less than - 50 °C.
[0067] Perform SEM detection on the protonated lithium nitride prepared in Example 1, and the results are as Figure 2 shown.
[0068] Preparation of the positive electrode: Use lithium nickel cobalt manganese (LiNi 0.8 Co 0.1 Mn 0.1 O2) as the active material, mix it evenly with a conductive agent (acetylene black) and a binder [polyvinylidene fluoride (PVDF)] in a mass ratio of 80:10:10, coat it on a carbon - coated aluminum foil, and dry it in a vacuum drying oven at 80 °C for 24 h to remove the solvent.
[0069] Preparation of the electrolyte: Dissolve 0.4 g of poly(vinylidene fluoride - hexafluoropropylene) (PVDF - HFP, weight - average molecular weight of 400000) and 0.4 g of LiFSI in 4 mL of DMF solution, stir at 50 °C for 8 h until completely dissolved, and pour the obtained solution evenly into a film. Then place it in a vacuum drying oven and dry it at 60 °C for 24 h to obtain a solid electrolyte.
[0070] Assembly of the test electrochemical window battery (half - cell): Assemble the battery in the order of negative electrode shell, gasket, solid electrolyte, coated and modified lithium sheet, and positive electrode shell to test the electrochemical window of the solid electrolyte.
[0071] Test the electrochemical window at room temperature for the coated and modified lithium metal half - cell assembled in Example 1, and the results Figure 3 are shown.
[0072] Assembly of the lithium metal symmetric battery: Assemble the Li||Li symmetric battery (lithium metal symmetric battery) in the order of negative electrode shell, coated and modified lithium sheet, solid electrolyte, coated and modified lithium sheet, and positive electrode shell to test the lithium metal stability and ion transference number.
[0073] The room-temperature lithium stability test was conducted on the assembled and coated-modified lithium metal symmetric battery in Example 1, and the results are as Figure 4 shown.
[0074] Assembly of lithium metal button cells: The positive electrode sheet, solid electrolyte, and coated-modified lithium metal were assembled into a lithium solid-state battery (button cell) for electrochemical performance testing.
[0075] The room-temperature electrochemical performance of the assembled and coated-modified lithium metal button cell in Example 1 was tested at 2C, and the results Figure 5 are shown.
[0076] Assembly of lithium metal pouch cells: The positive electrode sheet was cut into 43×56 mm, the coated-modified lithium metal was cut into 45×58 mm, and the solid electrolyte was cut into 50×65 mm. As Figure 6 shown, the laminates were stacked and sealed in an inert atmosphere in the order of positive electrode, solid electrolyte, and lithium metal, and then placed on the shelf for pouch cell cycle performance testing.
[0077] The room-temperature electrochemical performance of the assembled and coated-modified lithium metal pouch cell in Example 1 was tested at 0.2C, and the results Figure 7 are shown.
[0078] Example 2
[0079] Compared with Example 1, most of them are the same. The difference is that the calcination temperature in step (1) is 450°C for the first stage and 700°C for the second stage. The ion transference number, electrochemical window, and cycle performance of button and soft-pack batteries of this example were tested, and the test results are shown in Table 1.
[0080] Example 3
[0081] Compared with Example 1, most of them are the same. The difference is that the ultrasonic treatment time in the protonation process of step (2) is 1 h. The ion transference number, electrochemical window, and cycle performance of button and soft-pack batteries of this example were tested, and the test results are shown in Table 1.
[0082] Example 4
[0083] Compared with Example 1, most of them are the same. The difference is that the ultrasonic treatment time in the protonation process of step (2) is 3 h. The ion transference number, electrochemical window, and cycle performance of button and soft-pack batteries of this example were tested, and the test results are shown in Table 1.
[0084] Example 5
[0085] Compared with Example 1, most of them are the same. The difference is that the rotation speed of the spin coater in step (4) is 200 r / min and the spin coating thickness is 10 μm. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this example were tested, and the test results are shown in Table 1.
[0086] Example 6
[0087] Compared with Example 1, most of them are the same. The difference is that the rotation speed of the spin coater in step (4) is 600 r / min and the spin coating thickness is 30 μm. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this example were tested, and the test results are shown in Table 1.
[0088] Comparative Example 1
[0089] Compared with Example 1, most of them are the same. The difference is that the uncoated and modified lithium metal foil is directly used as the negative electrode. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0090] Assembly of the electrochemical window battery: Assemble the battery in the order of negative electrode case, gasket, solid electrolyte, coated and modified lithium sheet, and positive electrode case, and test the electrochemical window of the solid electrolyte.
[0091] The test results of the room-temperature electrochemical window of the assembled half-cells in Example 1 and Comparative Example 1 are as Figure 3 shown.
[0092] Comparative Example 2
[0093] Compared with Example 1, most of them are the same. The difference is that steps (1) and (2) are omitted, and a coating that does not introduce carbon nitride is used in step (3). The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0094] Comparative Example 3
[0095] Compared with Example 1, most of them are the same. The difference is that step (2) is omitted, no protonation treatment is performed, and the bulk carbon nitride prepared in step (1) is directly used in step (3). The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0096] Comparative Example 4
[0097] Compared with Example 1, most of them are the same. The difference is that step (1) is omitted, no thermal polymerization treatment is performed, and the melamine powder is directly protonated. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0098] Comparative Example 5
[0099] Compared with Example 1, most of them are the same. The difference lies in that for the calcination temperature in step (1), the first-stage calcination temperature is 400 °C and the second-stage calcination temperature is 650 °C. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0100] Comparative Example 6
[0101] Compared with Example 1, most of them are the same. The difference lies in that for the calcination temperature in step (1), the first-stage calcination temperature is 500 °C and the second-stage calcination temperature is 800 °C. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0102] Comparative Example 7
[0103] Compared with Example 1, most of them are the same. The difference lies in that for the ultrasonic treatment time during the protonation process in step (2), it is 4 h. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0104] Comparative Example 8
[0105] Compared with Example 1, most of them are the same. The difference lies in that for the rotation speed of the spin coater coating in step (4), it is 100 r / min and the spin coating thickness is 5 μm. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0106] Comparative Example 9
[0107] Compared with Example 1, most of them are the same. The difference lies in that for the rotation speed of the spin coater coating in step (4), it is 700 r / min and the spin coating thickness is 40 μm. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0108] Comparative Example 10
[0109] Compared with Example 1, most of them are the same. Steps (3) and (4) are omitted. The spin coater coating in step (4) is changed to a coating method, and the coating liquid is evenly coated on the surface of the solid electrolyte, controlling the coating thickness to be 20 μm and the standing time to be 8 h. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example were tested, and the test results are shown in Table 1.
[0110] Comparative Example 11
[0111] Compared with Example 1, most of them are the same. The difference lies in the use of protonated carbon nitride. Steps (3) and (4) are omitted. In step (3), the coating method is changed to molten lithium coating. Protonated carbon nitride is subjected to molten lithium perfusion under an argon atmosphere (oxygen content ≤ 0.01 ppm, water content ≤ 0.01 ppm, temperature is 350 °C), and then cooled to room temperature. The ion transference number, electrochemical window, and cycle performance of coin and soft-pack batteries of this comparative example are tested, and the test results are shown in Table 1.
[0112] According to Figure 6 the schematic diagram of
[0113] Table 1 Test results of relevant performances of each example and comparative example
[0114]
[0115] The ion transference number of the battery is tested by the potentiostatic polarization method (steady-state current method), the electrochemical window is tested by the linear sweep voltammetry method, and the test method for the capacity retention rate at 2C for 1200 cycles at room temperature refers to the relevant regulations of GB / T 18287. The test method for the cycle performance of the soft-pack battery refers to the relevant regulations of GB / T 31486-2015 "Requirements and Test Methods for Cycle Life of Power Batteries for Electric Vehicles".
[0116] As can be seen from Table 1, when the untreated modified lithium foil was used in Comparative Example 1, the ion transference number was 0.24, the electrochemical window was only 3.8 V, the Li||Li coin-type symmetric battery could only cycle for 57 h, and the solid-state lithium metal coin-type battery with the assembled NCM811 cathode experienced a capacity plunge at the 45th cycle under the condition of 2C at room temperature. From Comparative Example 2, it can be seen that if the coating without introducing carbon nitride was used, the ion transference number was 0.25, the electrochemical window was only 3.9 V, the Li||Li coin-type symmetric battery could only cycle for 83 h, and the solid-state lithium metal coin-type battery with the assembled NCM811 cathode experienced a capacity plunge at the 61st cycle under the condition of 2C at room temperature. This was because there was no ion conductivity of carbon nitride in the coating, and only the coating increased the path of ion migration, resulting in poor performance due to the large ion migration impedance. From Comparative Example 3, it can be seen that if unprotonated carbon nitride was introduced, the ion transference number was 0.47, the electrochemical window was only 4.2 V, the Li||Li coin-type symmetric battery could only cycle for 477 h, and the capacity retention rate of the solid-state lithium metal coin-type battery with the assembled NCM811 cathode was 6.17% after 1200 cycles under the condition of 2C at room temperature. Unprotonated carbon nitride could not be evenly dispersed in the solution and agglomerated, resulting in poor electrochemical performance. From Comparative Example 4, it can be seen that the unpolymerized melamine powder by thermal polymerization could not form a stable carbon nitride structure and could not effectively play its role in the interfacial protective layer. Comparative Examples 5 and 6 showed that too low calcination temperature would lead to insufficient crystallinity of carbon nitride and could not form a stable carbon nitride structure, while too high calcination temperature would lead to excessive decomposition or structural collapse of carbon nitride, resulting in changes in the pore structure of the material, affecting its ion conductivity and mechanical stability, and further affecting the performance of the solid-state battery. From Comparative Example 7, it can be seen that when the protonation treatment time was more than 4 h, the surface of carbon nitride was over-protonated, and the cycle performance of the solid-state battery decreased significantly. The capacity retention rate after 1200 cycles at 2C at room temperature was only 11.96%. Comparative Examples 8 and 9 showed that if the coating was too thin (less than 10 μm), it might not effectively protect the lithium metal anode, could not achieve a uniform lithium ion flux distribution, and thus could not effectively inhibit the growth of lithium dendrites. If the coating was too thick (more than 30 μm), it might increase the internal resistance of the battery, resulting in too long a lithium ion transport path and reduced ion transport efficiency. Comparative Example 10 showed that the uniformity of the interface layer could not be guaranteed by uniformly coating the surface of the solid electrolyte, which affected the ion transport path, and due to the compatibility problem between the precursor and the polymer matrix, the interface layer was prone to peeling and could not provide effective protection. From Comparative Example 11, it can be seen that by the method of carbon nitride coating molten lithium, the uniformity and compactness of the carbon nitride coating would affect the stability of the material, and the high-temperature melting reaction needed to be carried out in a glove box, with significant energy consumption cost and high process complexity, which was not conducive to large-scale production.
[0117] In Example 1, by introducing protonated carbon nitride in cooperation with a polymer to form a carbon nitride-polymer composite layer, excellent mechanical stability and ionic conductivity are achieved, realizing a high ion transference number (t Li + = 0.68), a wide electrochemical window (4.8 V), stable cycling of 2000 h for the Li||Li coin-type symmetric cell, a capacity retention rate of 82.97% for the assembled solid-state lithium metal coin-type battery with an NCM811 cathode at 2C at room temperature for 1200 cycles. In addition, a soft-pack battery assembled with a lithium foil modified with a carbon nitride-polymer coating realizes stable cycling of 160 cycles at 0.2C. Example 2 shows that the calcination temperature should be controlled within a certain range to ensure the structural stability and specific surface area of carbon nitride. Examples 3 and 4 show that the protonation time is controlled within 1 - 3 h to achieve uniform insertion of H + . Examples 5 and 6 show that the coating thickness should be controlled within 10–30 μm to balance the ion transport efficiency and mechanical stability.
[0118] It should be noted that the above examples are merely illustrations for clearly explaining the present invention and are not limitations on the implementation modes of the present invention. For those of ordinary skill in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to enumerate all implementation modes here. Any obvious changes or modifications derived from the technical solutions of the present invention still fall within the protection scope of the present invention.
Claims
1. A preparation method of protonated carbon nitride, characterized in that, It includes the following steps: Grind carbon nitride, soak it in an acidic solution, wash it until neutral, then ultrasonically treat, exfoliate, and dry the washed carbon nitride to obtain protonated carbon nitride.
2. The preparation method according to claim 1, characterized in that, The preparation method of the carbon nitride is: calcine melamine in segments under an inert atmosphere to obtain carbon nitride; The process of the segmented calcination is: the first-stage calcination temperature is 450 - 550 °C, the heating rate is 5 - 10 °C / min, and the time is 1 - 3 h; the second-stage calcination temperature is 600 - 750 °C, the heating rate is 5 - 10 °C / min, and the time is 1 - 3 h.
3. The preparation method according to claim 2, characterized in that, The flow rate of the inert gas is 40 - 60 mL / min; The inert gas is argon, nitrogen, or helium.
4. The preparation method according to claim 1, characterized in that, The acidic solution is hydrochloric acid; the concentration of hydrochloric acid is 3 - 6 mol / L; the soaking time in the acidic solution is 1 - 2 h; preferably, the carbon nitride is ground to a particle size of 25 - 75 μm; the process of ultrasonication is: working for 3 - 5 s, intermittent for 3 - 5 s, and the ultrasonication time is 1 - 3 h; the process of exfoliation is: mix the carbon nitride with salt and ball-mill, the ball-mill rotation speed is 400 - 700 r / min, and the ball-mill time is 2 - 4 h; The salt is one or more of sodium chloride, ammonium sulfate, and potassium chloride.
5. The preparation method according to any one of claims 1-4, characterized in that, The porosity of the protonated carbon nitride is 20% - 30%; the diameter of the micropores of the protonated carbon nitride is 0.5 - 1 nm.
6. Protonated carbon nitride prepared by the preparation method according to claims 1 - 5.
7. A polymer slurry, characterized in that, The polymer slurry contains the protonated carbon nitride according to claim 6.
8. The polymer slurry according to claim 7, characterized in that, The polymer slurry contains 1 - 5 parts of the protonated carbon nitride, 8 - 12 parts of an olefin polymer, and 3 - 8 parts of a lithium salt.
9. A lithium metal anode, characterized in that, The lithium metal negative electrode is coated with the polymer slurry according to claim 7 or 8.
10. A solid-state battery, characterized in that, The solid-state battery includes the lithium metal negative electrode according to claim 9.
Citation Information
Patent Citations
A three-dimensional lithium metal negative electrode material with a solid electrolyte interface and a preparation method thereof
CN114899362B
Method for modifying negative electrode interface in solid-state lithium battery by using composite two-dimensional material
CN117317385A
Method for ball mill peeling of graphite phase carbon nitride
CN109205580A
Carbon nitride and carbon coated NASICON type electrode material and preparation method thereof
CN110880590A
High-performance all-solid-state lithium battery and preparation method thereof
CN111952673A